Ciência, políticas públicas e inclusão social: debates sobre células-tronco no Brasil e no Reino Unido - Liliana Acero (Universidade do Estado do Rio de Janeiro, 2010)
This article analyzes the main rhetorical approaches, themes, and strategies in the contemporary public debate on stem cell research and therapies in Brazil. Based on previous studies, analysis of the transcripts from public hearings, newspaper clippings, and 15 semi-structured interviews with researchers, public policymakers, and representatives of organized civil society, the article discusses divergences and convergences between the proponents and opponents of such research. The results are compared to trends in the United Kingdom, a leading country in the field, concluding that the main difference between the two countries lies in the form of social inclusion and public participation.